Engineering Education for Forming Students’ Risk-Oriented Consciousness - G. Dolinina, Irina; K. Geykhman, Lyubov; V. Kushnaryova, Oksana; I. Kazarenkov, Vyacheslav (International Journal of Engineering and Technology, 2018)
The paper outlines the research on educational processes aimed at forming risk-oriented consciousness in students as an essential component of life safety culture. Risk-oriented consciousness formation in students attending a technical university is advisable in view of them getting ready for future professional activities and its advisability is the core idea of all the work done. The paper contains an authors' interpretation of "risk-oriented consciousness of students attending a technical university" concept. To achieve the research goal, the authors applied a design technique. As a result, an educational technology for forming risk-oriented consciousness in students was developed. The authors also highlight obvious prospects and necessity to get further insights into the problem under consideration.Â Â